Effect of single-dose dexmedetomidine on postoperative recovery after ambulatory ureteroscopy and ureteric stenting: a double blind randomized controlled study - Shariffuddin, Ina Ismiarti; Teoh, Wendy Hui Ling; Wahab, S.; Wang, Chew Yin (BMC, 2018)
Background: Ambulatory surgery has recently gain popularity, as it is a good method of optimizing hospital resources utilization. To support ambulatory surgery, anaesthetic goals now revolve around patients' early recovery with minimal pain and nausea, expedient discharge home and prompt resumption of activities of daily living. In this study, we evaluated the effect of a single pre-induction dose of dexmedetomidine on anaesthetic requirements, postoperative pain and clinical recovery after ambulatory ureteroscopy andureteric stenting under general anaesthesia. Methods: Sixty patients were randomised to receive IV dexmedetomidine 0.5 μg.kg-1 (Group DEX, n = 30) or IV saline (Group P, n = 30). General anaesthesia was maintained with Sevoflurane: oxygen: air, titrated to BIS 40-60. Pain intensity, sedation, rescue analgesics, nausea/vomiting and resumption of daily activities were recorded at 1 h, and postoperative day (POD) 1-5. Results: Group DEX patients had significant reduction in sevoflurane minimum alveolar concentration (MAC), mean (SD) DEX vs. Placebo 0.6 (0.2) vs. 0.9 (0.1), p = 0.037; reduced postoperative resting pain at 1 h (VAS 0-10) (mean (SD) 1.00 (1.84) vs. 2.63 (2.78), p = 0.004), POD 1 (mean (SD) 1.50 (1.48) vs. 2.87 (2.72), p = 0.002), POD 2 (0.53 (0.97) vs. 1.73 (1.96), p = 0.001) and POD 3 (0.30 (0.75) vs. 0.89 (1.49), p = 0.001). DEX patients also had less pain on movement POD 1 (3.00 (2.12) vs. 4.30 (3.10), p = 0.043) and POD 2 (2.10 (1.98) vs. 3.10 (2.46), p = 0.040), with higher resumption of daily activities by 48 h compared to placebo, 87% vs. 63%, p = 0.04. Conclusions: We conclude that a single dose of dexmedetomidine was a useful adjuvant in reducing MAC and postoperative pain (at 1 h and POD 1-3), facilitating faster return to daily activities by 48 h.